Role of Short Term Open Eye Orthok Lens Wear in Inducing Myopia Control Changes in Eyes with Moderate Myopia - Kulkarni Pancham1; Bandamwar Kalika (Indian Journal of Forensic Medicine & Toxicology, 2021)
Purpose: To assess peripheral refraction, corneal, and visual acuity changes after open eye use of orthokeratology (OrthoK) contact lenses. Methodology: OrthoK contact lenses were worn on separate occasions for half an hour and 2 hours in open eye condition. The peripheral refraction (PR) changes were assessed monocularly up to 30° nasally and temporally in the horizontal visual field using the open field autorefractometer. Average corneal power (ACP), central corneal thickness (CCT), and visual acuity (VA) was recorded using corneal topographer, specular microscope, and LogMAR chart respectively. Results: Mean baseline PR at 25° and beyond both nasally and temporally was -0.54 ± 1.68D (mean ± SD) which increased to mean -1.29 ± 1.43D (p < 0.01) post half an hour of lens wear and further increased to mean -1.62 ± 1.53D (p < 0.01) after 2 hours lens wear. The mean baseline ACP was 43.45 ± 1.34D that reduced to mean 43.11 ± 1.37D (p < 0.01) after half an hour of lens wear and a further reduction to mean 42.73 ± 1.34D (p < 0.01) 2 hours post lens wear. Mean CCT changes after half an hour lens wear were not significant but it reduced by mean 14.92 ± 4.68 µm (p < 0.01) 2 hours post lens wear as compared to baseline. The unaided VA improved from mean 0.85 + 0.37 log at baseline to mean 0.49 + 0.35 log (p < 0.01) after half an hour of lens wear and mean 0.39 + 0.35 log (p < 0.01) after 2 hours of OrthoK lens wear. Conclusion: Rapid corneal and peripheral refraction shifts are seen after half an hour of open-eye wear of the OrthoK lens with a gradual rise in impact for 2 hours of lens wear.